Peran Mediasi Dalam Penyelesaian Sengketa Harta Warisan Dalam Hukum Keluarga Islam - Muthi'ah; Adrina Fauza; Nazwa Ramadhani; Marwah Syaifani; Muhammad Hafiz Nur (Tabayyun : Journal Of Islamic Studies, 2024)
Settlement of disputes or confrontations that inevitably arise in society due to inheritance, giving rise to disputes and even conflicts between parties. The aim of this research is to determine the steps for resolving inheritance disputes in the Medan Class IA Religious Court as well as the function of mediation in these trials. Field research is the primary data source for the normative juridical research method used in this research. We can conclude that Law Number 7 of 1989 and Government Regulation (PERMA) Number 1 of 2016 are the basis for procedures for resolving inheritance disputes in the Medan Class IA Religious Court. The interested parties cannot be forced to resolve it through mediation. differences of opinion, then the task of mediation is to mediate until a mutually binding agreement is reached. For mediation to be successful, the mediation has the following functions: mediating between the parties, helping them find common ground regarding their problems, and supervising the mediation by arranging meetings, negotiations, and discussions as well as acting as a mediator and helping the parties reach an agreement.